2007
DOI: 10.1002/jso.20845
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors determining survival in differentiated thyroid cancer

Abstract: In DTC patients, in addition to traditional risk factors, prognostic factors, such as vascular invasion and capsular invasion, need to be evaluated; not only for achieving an adequate therapeutic approach, but also for avoiding overtreatment of low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 33 publications
(37 reference statements)
6
17
0
Order By: Relevance
“…Numerous studies have described the importance of Tg and TSH values for optimal accuracy of 18F-FDG-PET/CT [31][32][33][34][35][36]. Our results agree with previous studies.…”
Section: Discussionsupporting
confidence: 95%
“…Numerous studies have described the importance of Tg and TSH values for optimal accuracy of 18F-FDG-PET/CT [31][32][33][34][35][36]. Our results agree with previous studies.…”
Section: Discussionsupporting
confidence: 95%
“…On the other hand, the AMES (5) prognostic scoring system and various versions of the TNM (3, 4) system do not include histology as an independent risk factor. In various other studies, histology in some does (13,14), and in others does not (15) come out as an independent prognostic factor for survival in DTC. DeGroot et al (16) report that FTC patients have a considerably poorer prognosis than PTC patients; however, they do not report what happens when differences in disease stage at the time of presentation are compensated for.…”
Section: Discussionmentioning
confidence: 94%
“…By contrast, distant metastases, mainly to the lungs and bones, are more frequent at disease presentation (~20%) (4). Although former studies have indicated that FTCs, particularly the invasive form, have a poorer prognosis than PTCs (74,75), a recent study that evaluated more than 1,000 patients did not find differences in tumor-specific survival between PTC and FTC, after controlling for age, primary tumor size, extrathyroidal invasion or distant metastasis at diagnosis (76).…”
Section: Follicular Thyroid Carcinomamentioning
confidence: 84%